Stratigraphy, lithofacies and depositional environments of the Capitanian and Dzulfian strata (Permian) in the Glass Mountains, west Texas: An extended abstract - Haneef, Mohammad; Rohr, David M.; Wardlaw, Bruce R. (Journal of Himalayan Earth Sciences, 1994)
ABC